Microbe-Derived Indole Metabolite Demonstrates Potent Multidrug Efflux Pump Inhibition in Staphylococcus aureus - Tambat, Rushikesh; Jangra, Manoj; Mahey, Nisha; Chandal, Nishtha; Kaur, Manpreet; Chaudhary, Surbhi; Verma, Dipesh Kumar; Thakur, Krishan Gopal; Raje, Manoj; Jachak, Sanjay; Khatri, Neeraj; Nandanwar, Hemraj (Frontiers in Microbiology, 2019)
Efflux pumps are always at the forefront of bacterial multidrug resistance and account for the failure of antibiotics. The present study explored the potential of 2-(2- Aminophenyl) indole (RP2), an efflux pump inhibitor (EPI) isolated from the soil bacterium, to overcome the efflux-mediated resistance in Staphylococcus aureus. The RP2/antibiotic combination was tested against efflux pump over-expressed S. aureus strains. The compound was further examined for the ethidium bromide (EtBr) uptake and efflux inhibition assay (a hallmark of EPI functionality) and cytoplasmic membrane depolarization. The safety profile of RP2 was investigated using in vitro cytotoxicity assay and Ca2+ channel inhibitory effect. The in vivo efficacy of RP2 was studied in an animal model in combination with ciprofloxacin. RP2 exhibited the synergistic activity with several antibiotics in efflux pump over-expressed strains of S. aureus. In the mechanistic experiments, RP2 increased the accumulation of EtBr and demonstrated the inhibition of its efflux. The antibiotic-EPI combinations resulted in extended post antibiotic effects as well as a decrease in mutation prevention concentration of antibiotics. Additionally, the in silico docking studies suggested the binding of RP2 to the active site of modelled structure of NorA efflux pump. The compound displayed low mammalian cytotoxicity and had no Ca2+ channel inhibitory effect. In ex vivo experiments, RP2 reduced the intracellular invasion of S. aureus in macrophages. Furthermore, the RP2/ciprofloxacin combination demonstrated remarkable efficacy in a murine thigh infection model. In conclusion, RP2 represents a promising candidate as bacterial EPI, which can be used in the form of a novel therapeutic regimen along with existing and upcoming antibiotics, for the eradication of S. aureus infections.